New diatoms (Bacillariophyta) from western North America - Bahls, Loren (Phytotaxa, 2013)
Twelve new species of diatoms are described from material collected in Colorado, Montana, Oregon, Washington, and Wyoming, USA, and in Alberta and British Columbia, Canada. The new species are Cavinula davisiae, Craticula johnstoniae, Craticula sardiniana, Cymatopleura internationale, Cymbella cosleyi, Cymbopleura edlundii, Gomphonema johnsonii, Navicula supleeorum, Navicula trilatera, Neidium bobmarshallensis, Stauroneis boyntoniae, and Staurophora columbiana. Two varieties are elevated to species: Neidium fogedii (replaced synonym: N. kozlowii var. densestriata) and Neidium undulatum (replaced synonym: N. kozlowii var. undulata). Two species are transferred to new genera: Cymbella rainierensis to Cymbopleura and Navicula soodensis to Staurophora. An Alberta population of Neidium inconstans representing significant morphological variation and range extension for this species is also presented. Water quality preferences of these taxa run the gamut from ultraoligotrophic to hypereutrophic and fresh water to hypersaline. Thirteen of these taxa are either local or Northwest regional endemics. Four of these taxa are members of the Holarctic diatom flora or they are cosmopolitan.